A DESCRIPTIVE ANALYSIS OF TEACHER TALK IN LEADING THE TEACHING LEARNING ACTIVITIES THROUGH THE STAGES OF SCIENTIFIC APPROACH: A Case Study in A Junior High School in Bandung - Muttaqin, Ganjar (2015)
In the 2013 Curriculum, scientific approach which consists of observing, questioning, experimenting/collecting, associating and networking/ communicating is the compulsory approach to teaching learning activities. However despite trainings for teachers held by the government in relation to this approach, the teachers still need an example of its implementation which they can learn from. This study is aimed to describe how a teacher led the teaching learning activities following the stages of scientific approach. The study was conducted in a school in Bandung. Therefore this study is a descriptive case study. The object of the study is teacher talk of a teacher in three sessions. The raw data from teacher talk were collected through observations and interviews which were videotaped and audio-taped. The recordings were then transcribed. After being transcribed, the data of teacher talk and interviews were further codified so that the final data were those relevant with the implementation of scientific approach. Teacher talk was then analyzed using features of Systemic Functional Linguistics in terms of metafunctions implied in the register used in the classroom to describe how it could lead the teaching learning activities using scientific approach. The analysis shows that in the teaching learning activities, teacher talk can be analyzed in terms of regulative register with which how the pace of activities and students' behavior were regulated and instructional register with which the content material was delivered. It is hoped that the description of teacher talk in this case study can give an illustration of how the scientific approach can be facilitated through teacher talk for fellow teachers and the analysis of teacher talk using the features of Systemic Functional Linguistics can enrich the literature of classroom discourse analysis. Keywords : teacher talk, scientific approach, systemic functional linguistics   Di dalam Kurikulum 2013, pendekatan ilmiah yang terdiri dari mengamati, mempertanyakan, mengumpulkan, menalar, dan mengkomunikasikan adalah pendekatan wajib untuk kegiatan belajar mengajar. Namun, terlepas dari banyaknya pelatihan untuk guru oleh pemerintah dalam kaitannya dengan pendekatan ini, para guru masih memerlukan suatu contoh implementasi yang bias mereka pelajari. Penelitian ini ditujukan untuk menjelaskan bagaimana seorang guru memandu kegiatan belajar mengajar dengan mengikuti tahap-tahap pendekatan ilmiah. Penelitian ini dilaksanakan di sebuah SMP di Bandung. Karena itu ini adalah penelitian studi kasus. Obyek penelitian adalah teacher talk dalam tiga pertemuan. Data mentah dari teacher talk dikumpulkan melalui observasi dan wawancana yang direkam video dan audionya. Rekaman tersebut kemudian ditranskripsikan. Setelahnya, data teacher talk dan wawancara dikodifikasi lebih lanjut sehingga data akhir adalah data yang relevan dengan penerapan pendekatan ilmiah. Teacher talk kemudian dianalisa dengan menggunakan fitur-fitur Systemic Functional Linguistics dalam hal metafunctions yang terkandung di dalam register yang digunakan di dalam kelas untuk menjelaskan bagaimana teacher talk ini bias memandu kegiatan belajar mengajar dengan menggunakan pendekatan ilmiah. Hasil analisa menunjukkan bahwa di dalam kegiatan belajar mengajar, teacher talk bisa dianalisa dari sisi regulative register yang menjadi alat mengatur laju aktivitas dan perilaku siswa dan instructional register yang menjadi sarana penyampaian materi pelajaran. Diharapkan bahwa penjelasan teacher talk dalam studi kasus ini bias memberikan ilustrasi bagaimana pendekatan ilmiah bisa difasilitasi melalui teacher talk untuk para rekan guru dan analisa teacher talk dengan menggunakan fitur-fitur Systemic Functional Linguistics bias memperkaya khasanah analisa wacana kelas. Keywords : teacher talk , pendekatan ilmiah, systemic functional linguistics